International principles and standards for the practice of ecological restoration. Second edition - Gann, G.D.; McDonald, Tein; Walder, B.; Aronson, J.; Nelson, C.R.; Jonson, J.; Hallett, J.G.; Eisenberg, C.; Guariguata, M.R.; Liu, J.; Hua, F.; Echeverría, C.; et al. (WILEY, 2019)
EXECUTIVE SUMMARY